A new species of the Chaoborus flavicans complex (Diptera, Chaoboridae) in South Korea - Bang, Woo Jun; Shin, Seunggwan (Zootaxa, 2023)
Using reverse taxonomy and morphological analyses, this study describes a new species belonging to the C. flavicans species complex in the Korean Peninsula, Chaoborus pseudoflavicans Bang & Shin sp. nov. Descriptions of the new species from larvae to adults are provided, and the key to the C. flavicans species complex is updated accordingly. DNA barcodes (COI partial sequences) are shown to be sufficient for molecular identification in the C. flavicans species complex. Finally, the taxonomic accounts of all species in the C. flavicans complex are completely resolved for the first time.